Financial Accounting Information System With Method Commonsize To Know Financial Performance - Sindhu Rakasiwi; Haryo Kusumo; Yuli Fitrianto (Universitas PGRI Semarang, 2022)
PT XXX which is located on Jl. Pantura Semarang- Kendal, KawayuhanWest, Nolokerto, Kaliwungu District, Kendal Regency, Central JavaCompanies that sell building materials for the construction of buildings androad construction. Some of the building materials are self-produced such as gravel andconcrete. PT. XXX is still using the help of MSrecord financial data. And in the calculations stillusing the manual method, which must be calculated one by one. In compilingthe report is not yet structured. So that the company in readingfinancial statements still use the estimation method. Which if it continuescan cause losses to the company due to performance calculationsfinance.This study designs a financial accounting information system withcommonsize method to determine the financial performance of web-based companies.Which uses the PHP and MySQL programming languages. The purpose of existenceThe system can help companies perform financial calculationscompany and conduct financial performance analysis. It enables a company to well manage their financial performance